KAJIAN PREFERENSI KONSUMEN BERAS “IR 64” DAN FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT KONSUMSINYA DI KOTA BENGKULU - Reyendra, Ahmad (Jurnal AGRISEP, 2007)
The objective of this research were ; 1) to know  the level of consumer preference toward IR 64 rice and it’s related with the level of IR 64 nice consumption in Bengkulu city; 2) to know the factors the influence the level of IR 64 rice consumption in Bengkulu City. This research conducted in 4 big market in Bengkulu City  like pasar Minggu, Panorama market, Baru Koto market, and Pagar Dewa market. Accidental sampling method used to determined the number of sample. The information, that used in this research based on primary and secondary data. Analysis method that used in this research were rank spearman correlation test and multiple regression  test. The result of this research shown that most of consumer was in “very like” of preference level. The result of analysis shown that most of consumer was in “agree” of preference level or attribute like taste, smell, color, texture, packaging and easy for getting, price and quality. While, for attribute like proudly and practice most of consumer was in “disagree” of preference level. Multiple regression analysis shown that the factors like income and number of family member influence the consumption of IR 64 rice while the factors like price of IR 64 and price of other variety of rice uninfluenced the consumption of IR 64. Keyword : Rice, IR 64, preference, consumption, rank spearman correlation test and multiple regression.